2001
DOI: 10.1177/109442810144001
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Solution for Approximating the Power to Detect Effects of Categorical Moderator Variables Using Multiple Regression

Abstract: Investigators in numerous organization studies disciplines are concerned about the low statistical power of moderated multiple regression (MMR) to detect effects of categorical moderator variables. The authors provide a theoretical approximation to the power of MMR. The theoretical result confirms, synthesizes, and extends previous Monte Carlo research on factors that affect the power of MMR tests of categorical moderator variables and the low power of MMR in typical research situations. The authors develop an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 35 publications
1
96
0
Order By: Relevance
“…The moderated multiple regression approach we used is the optimal method for examining interaction effects between a categorical predictor variable (in the current study, sex) and a continuous moderating variable (age). The power of such analyses is affected by several factors including variability of the predictor variables; measurement error; total sample size; and unequal group size (Aguinis et al 2001). In the current study measurement error was minimal, due to the use of demographic predictor variables and psychometrically sound symptom measures.…”
Section: Discussionmentioning
confidence: 99%
“…The moderated multiple regression approach we used is the optimal method for examining interaction effects between a categorical predictor variable (in the current study, sex) and a continuous moderating variable (age). The power of such analyses is affected by several factors including variability of the predictor variables; measurement error; total sample size; and unequal group size (Aguinis et al 2001). In the current study measurement error was minimal, due to the use of demographic predictor variables and psychometrically sound symptom measures.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that MMR suffers from low statistical power (Aguinis, Boik, & Pierce, 2001;Aguinis, Culpepper, & Pierce, in press). Low statistical power means that, when they exist, the probability that population effects will be detected in the sample is low.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the power of our results was close or above the .80 value recommended (Cohen, 1992), and clearly exceed values found in previous research. For example, Aguinis, Boik, and Pierce (2001) found that the power to detect interaction effects in a typical study is .20 to .34. On the other hand, the effect sizes found in the current study were small.…”
Section: Strengths and Limitationsmentioning
confidence: 99%